KARAKTERISTIK PASIEN HIPERTENSI DI POLIKLINIK PENYAKIT DALAM RUMAH SAKIT UMUM DAERAH DR. H. CHASAN BOESOIRIE TERNATE - YUDISTIRA PUTRI PERTIWI; EKO SUDARMO Prihanto; edwin ambar (Kieraha Medical Journal, 2020)
Background: Major risk factor for cardiovascular disease is a hypertension. Hypertension is characterized by an increase in blood pressure ≥140/90mmHg in two measurements in calm conditions. The causes of hypertension are primary hypertension with unknown causes (90%) and secondary hypertension due to kidney disease or hormonal abnormalities in patients using contraception. According to world Health Organization people in the world suffer from hypertension 1.13 billion. It is estimated it will increase to 1.56 billion that in 2025. lifestyle is one of the factors that contribute to the prevalence of hypertension. Methode: This research is a cross sectional descriptive study that using secondary data obtained from medical record of hypertension patients at the internal medicine polyclinic of RSUD. Dr. H. Chasan Boesoirie Ternate in Januari until Desember 2019 to determine the characteristics of patients with hypertension. This research uses total sampling technique. Result and Conclusion: The results found 125 patients hypertension there were more men (54.4%) than female patients (45.6%), with a higher age percentage of ≥65 years (33.6%), and more patients with hypertension. type 1 (41.6)%), The most common causes of hypertension are primary hypertension patients (10.6%), most drug use is the CCB amlodipine group (82.4%), and most hypertensive patients use BPJS financing (64.8%) than independent costs (35.2%). Keywords: Hypertension, Characteristics, Polyclinic